Examining Treatment Options in Youth With Major Depressive Disorder: Observations From the TX‐YDSRN Registry Study - Emine Rabia Ayvaci; Karabi Nandy; Ryan Becker; Laura Stone; Abu Minhajuddin; Holli Slater; Lynnel C. Goodman; Sarah M. Wakefield; Eric A. Storch; Joseph C. Blader; Cesar A. Soutullo; Graham J. Emslie; et al. (Psychiatric Research and Clinical Practice)
Objective Treatment decisions for depression are a complex process, influenced by factors such as clinical characteristics, socioeconomic factors, and patient/caregiver preferences. This study examines the characteristics of treatment options during the first month of enrollment among depressed youth. Methods Data for 646 depressed youth were extracted from the Texas Youth Depression and Suicide Research Network study. Participants' treatments during the first month were categorized as no treatment (NT), psychotherapy only (THER), pharmacotherapy only (MED), or a combination of psychotherapy and pharmacotherapy (COMB). Sociodemographic and clinical features were compared across these treatment types. Results 7% were on NT, 5% on THER, 35% on MED, and 53% on COMB. The MED group was more likely to have low income compared to the COMB group. Compared to the MED group, COMB treatment had higher depression severity and suicidality. The NT group showed higher rates of social risk compared to the group with COMB. Treatment groups did not differ significantly in sex or race. When treatment preferences were examined, 40% of youth on MED expressed a preference for COMB treatment. Conclusions Treatment options vary with demographic characteristics, depression severity, suicidality, and high‐risk social factors. The finding that youth on MED are more likely to have low income compared to COMB treatment, despite a preference for COMB treatment among many, may suggest a potential barrier to accessing comprehensive treatment options. Relevance to Clinical Practice Findings highlight the need to address barriers to combination treatment, which is preferred by youth and caregivers for managing depression.